The spectrum of acute and chronic consequences of neurotrauma in professional and amateur boxing – A call to action is advocated to better understand and prevent this phenomenon - Michele Da Broi; Abdullah Al Awadhi; Philippe Voruz; Aria Nouri; Karl Schaller (Brain and Spine, 2024)
Introduction: Despite changes in regulations, boxing-related injuries and fatalities are still occurring. The numbers available in the literature regarding mortality and long-term consequences may not accurately represent the actual situation. Indeed, the real extent of this phenomenon remains poorly known. Research question: Delineating the spectrum of acute and chronic consequences of boxing-related traumatic brain injuries (TBI). Material and methods: Narrative review of the literature concerning acute and chronic boxing-related TBI. Keywords such as mortality, boxing, subdural hematoma were used to search in PubMed and Google scholar. An updated analysis of the Velazquez fatalities collection in boxing was undertaken. Results: The Velazquez collection includes 2076 fatalities from 1720 to the present with a death rate of 10 athletes per year. More than half of the deaths (N = 1354, 65.2%) occurred after a knock-out, and nearly 75% happened during professional bouts. In Australia, from 1832 to 2020, 163 fatalities were recorded (75% professional). In Japan, from 1952 to 2016, 38 deaths were recorded with a mean age of 23.9 years. Up to 40% of retired professional boxers in the United States were diagnosed with symptoms of chronic brain injury. Clinical dementia is far more prevalent among professional boxers than in amateurs with an incidence of 20%. Discussion and conclusions: A concerted effort to raise awareness and shed light on boxing-related neuro-trauma is required. Similar considerations can be made for other combat sports or contact sports. A call to action to address this knowledge gap, decrease and prevent this phenomenon is advocated.